Engaging a Dark Side Perspective: Integration of Second Wave Positive Psychology and Transformative Learning Theory - Adam L McClain (Adult Education Research Conference, 2025)
This paper explores transformative learning's emotional complexities through a dark side perspective, examining how emotional challenges foster personal growth and meaning-making in adult learning by navigating disorienting dilemmas.
Keywords: transformative learning; dark side; emotions; adult learning